1999
DOI: 10.1093/bja/82.3.360
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude and time course of impaired primary haemostasis after stopping chronic low and medium dose aspirin in healthy volunteers

Abstract: Aspirin ingestion within the previous 7-10 days is often considered a relative contraindication to performing invasive procedures. However, aspirin is an important component of many patients' treatment and withholding therapy for this time may be dangerous. To measure both the magnitude of the impairment in primary haemostasis induced by aspirin and how much recovery of platelet function occurs within 48 h of stopping aspirin, we studied serial changes in bleeding time (BT) in a randomized, double-blind, place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…When discontinuation was unavoidable, it seems practically important to make the duration of discontinuation as short as possible, since the majority of ST events were reported to have occurred beyond 1 week after discontinuation of APT [11]. Since bleeding time was reported to recover to the baseline level after 3-5 days of aspirin cessation, discontinuation of aspirin 3-5 days before surgical procedures would be long enough to minimize bleeding risk when discontinuation of aspirin is unavoidable [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…When discontinuation was unavoidable, it seems practically important to make the duration of discontinuation as short as possible, since the majority of ST events were reported to have occurred beyond 1 week after discontinuation of APT [11]. Since bleeding time was reported to recover to the baseline level after 3-5 days of aspirin cessation, discontinuation of aspirin 3-5 days before surgical procedures would be long enough to minimize bleeding risk when discontinuation of aspirin is unavoidable [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…36,37 However, considering the risk of thromboembolism, there are reports that a shorter cessation period may be sufficient. 13,15 Some reports have evaluated hemostasis after the stopping of ASA; 12,14,38 however, there are few such reports on TP or combined therapy. 12,39 We studied the effect of ASA, TP, and a combination regimen on primary hemostasis in healthy volunteers.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Only a few studies have actually studied whether here should be a cessation period, and if so, its optimal duration, for various anti-platelet agents prior to endoscopic procedures. [11][12][13][14][15] In order to minimize the risk of bleeding complications due to the administration of anti-platelet agents versus the risk of thromboembolism due to the cessaBackground. Anti-platelet agents are widely used for the treatment and prevention of thrombotic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the wide variability and lack of specificity of this test, its use in the detection of blood dyscrasia is limited. nevertheless, Bt test remains useful in the preoperative assessment of patients with haemostatic disorders (21). in the present study, Bt was examined preoperatively.…”
mentioning
confidence: 92%
“…An association between the use of ASA and bleeding outcome measures was not identified. Moreover, Sonksen, et al showed that the increase in Bt caused by daily ASA in doses of up to 300 mg did not exceed normal limits in most patients (21). thus, patients need not to stop taking ASA before dental surgery, as the hemorrhagic risk is not greater than the thromboembolic risk associated with interruption of the drug regimen.…”
mentioning
confidence: 99%